The Quality of Urban Living - Böhm, Aleksander (Journal of Public Governance, 2021)
Objectives: This paper presets the different factors of living in an urban space, as well as their implications.Research Design & Methods: The mosaic of the different ways of living in a modern city is currently influenced by a new phenomenon (till now only partially recognised), namely the advancement of information technology. The article assumes the form of the overview of the history of the development of modern city.Findings: Comparing and estimating different results of urban innovations can serve as the best practice for urban planning.Implications / Recommendations: Eliminating the disadvantages and retaining the main advantage of a “flat with own garden” – now called smart sprawl – seems to be a permanent and long-lasting tendency.Contribution / Value Added: The paper is a contribution to the list of the contemporary problems such as urban sprawl, Transport-Oriented Development, telecommuting, and the role of the public space.